Transformations the Seats of Rural Communes into Cities – Expectations of Local Authorities in the Context of Urbanization - Szymańska, Justyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
Nowadays, urbanization is an increasingly common phenomenon. In many countries, the number of cities and urban population is steadily increasing. Therefore, the topic of attention becomes the search for the reasons for the transformation of rural communes’ seats into cities. Local authorities are the main initiators of these changes, therefore the expectations of local authorities regarding them are also interesting. The main objectives of the article are to identify the expectations of local authorities related to the transformation of the seats of rural communes into cities and to determine to what extent this change affects the benefits expected by local authorities. Motivations for transformations and the expected benefits resulting from them were analyzed on the example of seven communes in Poland: Urzędów, Mielno, Wiślica, Radoszyce, Otyń, Łagów, Józefów nad Wisłą. For this purpose, the characteristics of selected communes were made, and then, using a structured interview, the reasons for the change of the seat of the commune and the expectations of the local authorities were indicated. The conducted research shows that in most cases the local authorities expect mainly the increase in the prestige of the town and the acquisition of new sources of financing.